A review on the emerging resilient and multifunctional ceramic aerogels. (10th June 2021) - Su, Lei; Niu, Min; Lu, De; Cai, Zhixin; Li, Mingzhu; Wang, Hongjie
Abstract: Ceramic aerogels are attractive for their low density, high porosity, large surface area as well as various applications in areas of thermal insulation, catalysis, filtration, and lightweight structural materials. Conventional ceramic aerogels are usually assembled by oxides nanoparticles. Due to the inefficient neck-like connections between the nanoparticles and the volume shrinkage at elevated temperatures, ceramic aerogels fail easily caused by the brittleness and high-temperature structural collapse. To overcome these drawbacks, a class of resilient ceramic aerogels with highly porous architectures that are composed of one- or two-dimensional nanostructures has been prepared. Benefiting from the unique microstructures and/or the high-temperature stability of their building blocks, these aerogels exhibit reversible compressibility, high-temperature stability, thermal insulation, and various functions. In this review, we introduced the preparation methods, microstructures, mechanical properties, high-temperature stability, thermal insulation and various functions of these resilient ceramic aerogels. We have also discussed the relationships between their microstructures and properties, including mechanical properties and thermal insulation performance. Finally, perspectives for the further development of resilient ceramic aerogels are presented.